2016
DOI: 10.1590/1982-0224-20140134
|View full text |Cite
|
Sign up to set email alerts
|

Zoogeography of Elasmobranchs in the Colombian Pacific Ocean and Caribbean Sea

Abstract: In order to investigate zoogeographical patterns of the marine elasmobranch species of Colombia, species richness of the Pacific and Caribbean and their subareas (Coastal Pacific, Oceanic Pacific, Coastal Caribbean, Oceanic Caribbean) was analyzed. The areas shared 10 families, 10 genera and 16 species of sharks, and eight families, three genera and four species of batoids. Carcharhinidae had the highest contribution to shark richness, whereas Rajidae and Urotrygonidae had the greatest contribution to batoid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Hypanus marianae in Brazil occupies a trophic level (TL = 3.6) similar to H. americanus (TL = 3.52) in the Caribbean (Tilley et al, 2013), Urotrygon aspidura (TL = 3.7) and U. rogersi (TL = 3.5) in Colombia (Navia et al, 2016), N. kuhlii (TL = 3.58), Neotrygon annotata (TL = 3.57), and Neotrygon picta (TL = 3.55) in Australia (Jacobsen & Bennett, 2012), Rhinoptera bonasus (TL = 3.4) in Brazil (Bornatowski et al, 2014) and Myliobatis goodei (TL = 3.2) in Patagonia (Molina & Cazorla, 2015), because their diet is based mainly on invertebrates. Similarly, to other Myliobatiformes mesopredators (O'Gorman & Emmerson, 2009), H. marianae can play an important ecological role in the environment, controlling the populations of reef invertebrates used as prey, and being food source of other species (Vaudo & Heithaus, 2011) such as reef sharks (Costa et al, 2015) and other stingrays such as H. americanus (Branco-Nunes et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Hypanus marianae in Brazil occupies a trophic level (TL = 3.6) similar to H. americanus (TL = 3.52) in the Caribbean (Tilley et al, 2013), Urotrygon aspidura (TL = 3.7) and U. rogersi (TL = 3.5) in Colombia (Navia et al, 2016), N. kuhlii (TL = 3.58), Neotrygon annotata (TL = 3.57), and Neotrygon picta (TL = 3.55) in Australia (Jacobsen & Bennett, 2012), Rhinoptera bonasus (TL = 3.4) in Brazil (Bornatowski et al, 2014) and Myliobatis goodei (TL = 3.2) in Patagonia (Molina & Cazorla, 2015), because their diet is based mainly on invertebrates. Similarly, to other Myliobatiformes mesopredators (O'Gorman & Emmerson, 2009), H. marianae can play an important ecological role in the environment, controlling the populations of reef invertebrates used as prey, and being food source of other species (Vaudo & Heithaus, 2011) such as reef sharks (Costa et al, 2015) and other stingrays such as H. americanus (Branco-Nunes et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Information reviewed included general works, such as Compagno () and Froese and Pauly (), reports of slepper shark in the Gulf of Mexico and Cuba (Benfield et al, ; Benz et al, ; Espinosa, ; Moreno & Pol, ), basic Colombian documents such as Mejia‐Falla, Navia, Mejía‐Ladino, Acero, and Rubio (), Grijalba‐Bendeck, Acero, Díaz‐Trujillo, and Gómez (), Caldas et al (), Mejia‐Falla, Navia, and Puentes (), and Navia, Mejía‐Falla, & Hleap, ). None of those Colombian studies reported sleeper sharks from the Colombian Caribbean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Son relativamente conocidos en el Caribe colombiano, donde se hallan representados por unas siete especies (Mok, et (Navia, et al, 2016) y 41 de ellas (33%) se hallan amenazadas o próximas a estarlo, es evidente que estos animales se encuentran cerca de ser removidos de nuestros mares, urgiéndose medidas apropiadas del Estado colombiano. Se considera que dos órdenes agrupan a la mayoría de los condrictios amenazados en Colombia: Carcharhiniformes y Rhinopristiformes.…”
Section: Artículo De Posesiónunclassified